(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this paper, an optimization problem is formulated for determining the optimal reactive power management strategy, for a microgrid, based on the reactive power support provided by the inverters from photovoltaic power plants (PVPPs). The optimization problem is solved by applying a recent and performant metaheuristic, namely the Sine-Cosine Algorithm. Multiple scenarios are defined, depending on the load and PVPP active power output, and the results obtained by the proposed strategy are presented in comparison with a reactive power management strategy based only on capacitor banks (CBs).